0301 Different Indices of Vigilant Attention During Sleep Deprivation: Evidence of Multiple Vigilance Constructs?. (27th May 2020) - Lawrence-Sidebottom, D; Hinson, J M; Whitney, P; Honn, K A; Van Dongen, H
Abstract: Introduction: Total sleep deprivation (TSD) causes profound vigilant attention deficits, with large, trait-like individual differences, as evidenced convincingly by response lapses on the psychomotor vigilance test (PVT). There is debate, however, about the role of vigilant attention deficits in the effects of TSD on other speeded performance tasks besides the PVT. We addressed this issue by testing whether PVT response lapses are related to delays in responding to stimuli under strict deadlines in two decision making tasks. Methods: N=54 healthy adults (aged 21-38y; 31 females) completed an in-laboratory TSD study. Following a 10h baseline sleep opportunity, cognitive testing occurred after 25h and 29h of TSD (09:00 and 13:00). Testing included an AX continuous performance task with switch (AX-CPTs), which is a dynamic decision making task requiring subjects to respond to a frequently occurring cue-probe combination; an identical pairs continuous performance task (CPT-IP), which is a 1-back go/no-go task; and a 10min PVT. Lapses (RTs>500ms) on the PVT and target accuracy on the AX-CPTs and CPT-IP were calculated as indices of vigilant attention. Intraclass correlation coefficients (ICCs) were used to quantify the stability of individual differences, and absolute rank-order correlation (| ρ |) was used to compare the three indices. Results: The stability of individual differences ranged from fair to substantial (PVT: ICC=0.44; AX-CPTs: ICC=0.73; CPT-IP: ICC=0.31). The rank-order correlation between the AX-CPTs and CPT-IP vigilant attention indices was relatively high (| ρ |=0.44), whereas correlations with PVT lapses were much lower (AX-CPTs: | ρ |=0.14; CPT-IP: | ρ |=0.04). Conclusion: Individual differences during TSD were moderately stable for each index of vigilant attention, but the relationships between PVT lapses and the other indices were weak. This suggests that any or all of the indices considered here are not pure measures of vigilant attention, or that vigilant attention may constitute multiple, distinct constructs. Support: CDMRP grant W81XWH-16-1-0319